Analisis produksi dan kualitas telur ayam ras petelur yang ada di Kabupaten Sorong: Analysis of Production and Quality of Commercial Layer Chicken Eggs in Sorong Regency - Nauw, Magriet B. H.; Hartini, Sri; Suawa, Elfira Kariane (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2024)
Abstract  Sorong Regency is the food barn of Sorong Raya, which includes Sorong Regency, South Sorong Regency, Sorong City, Maybrat Regency, Tambrauw Regency, and Raja Ampat Regency. The egg production of Sorong Regency is used to meet the needs of Sorong Regency as well as the Greater Sorong area, including Sorong City, South Sorong Regency, and Raja Ampat Regency. This study aims to analyze the production or performance of laying hens and evaluate the quality of eggs laid by hens in Sorong Regency. The method used in this research is the descriptive method, involving data collection techniques based on direct observation in the field, interviews with farmers, laboratory testing, and observation. Eight farmers were interviewed, and egg samples were taken to be tested for their quality. The average number of eggs taken from each farmer was 30 eggs per week, totaling between 117 and 120 eggs. The variables observed included 1) Performance, which involved feed consumption, feed conversion, and depletion. 2) Hen Day Production (HDP), and 3) Egg quality. The collected data were processed and presented in tables to determine the total and average values. Correlation tests were applied to examine the relationship between hen age and egg production, external egg quality, which includes egg weight, egg shape index, shell weight, shell thickness, and internal egg quality, including yolk color and Haugh unit. The study results revealed that 1) Hen Day Production of laying hens in Sorong Regency is still below the normal standard of daily egg production for ISA Brown laying hens. 2) On average, feed consumption and total depletion of laying hens in Sorong Regency are within the standard range, but the feed conversion value is still high and has not met the standard feed conversion value for ISA Brown laying hens. 3) Based on data on egg weight, IBT, shell weight, and shell thickness, the external egg quality of laying hens in Sorong Regency, according to BSN (3926: 2008), falls into the Medium category. Meanwhile, based on data on Air Cavity Depth, Yolk Color, and Haugh Unit, the internal quality of eggs from laying hens in Sorong Regency, according to BSN (3926: 2008), falls into Quality I. Keywords: Egg production; Egg quality; ISA Brown laying hens; Sorong Regency,   Abstrak  Kabupaten Sorong merupakan lumbung pangan Sorong Raya yang meliputi Kabupaten Sorong, Kabupaten Sorong Selatan, Kota Sorong, Kabupaten Maybrat, Kabupaten Tambrauw dan Kabupaten Raja Ampat.  Produksi telur ayam ras Kabupaten Sorong digunakan untuk menyuplai kebutuhan Kabupaten Sorong serta kebutuhan daerah Sorong Raya antara lain Kota Sorong, Kabupaten Sorong Selatan, dan Kabupaten Raja Ampat. Penelitian ini bertujuan untuk menganalisis produksi atau performa ayam ras petelur serta menganalisis kualitas telur ayam ras petelur di Kabupaten Sorong. Metode yang digunakan dalam penelitian ini metode deskriptif dengan teknik pengumpulan data berdasarkan observasi langsung di lapangan dan wawancara dengan peternak serta pengujian dan pengamatan di laboratorium. Delapan orang peternak diwawancara dan ambil sampel telur untuk diuji kualitas telur. Jumlah telur yang diambil rata-rata 30 butir/minggu dari peternak, sehingga total telur yang diambil dari masing-masing peternak berkisar 117-120 butir. Variabel yang diamati 1) Performa meliputi konsumsi pakan,  konversi pakan dan deplesi. 2) Hen Day Production (HDP) dan 3) Kualitas telur. Data yang diperoleh diolah dan ditampilkan dalam tabel untuk kemudian dicari jumlah dan rata-rata nilai. Uji korelasi diberlakukan untuk melihat korelasi antara umur ayam dengan produksi telur, kualitas telur ekternal yang meliputi; berat telur, indeks bentuk telur, berat kerabang, ketebalan kerabang, dan kualitas telur internal yang meliputi: warna kuning telur dan Haugh unit. Hasil penelitian diperoleh 1) Produksi telur harian (Hen Day Production) ayam ras petelur di Kabupaten Sorong masih dibawah standar normal produksi telur harian ayam petelur ISA Brown, 2) Secara rataan konsumsi pakan dan total deplesi ayam ras petelur di Kabupaten Sorong masih sesuai dengan standar konsumsi pakan dan total deplesi ayam ras petelur, namun nilai konversi pakan masih tinggi atau belum memenuhi standar nilai konversi pakan ayam petelur ISA Brown dan  3) Menilik data Berat telur, IBT, berat dan tebal kerabang, maka kualitas telur eksternal ayam ras petelur Kabupaten Sorong berdasar BSN (3926:2008) termasuk pada kategori Sedang, sedangkan berdasarkan data Kedalaman Rongga Udara, Warna Kuning Telur dan Haugh Unit maka kualitas internal telur ayam ras Petelur Kabupaten Sorong berdasarkan BSN (3926:2008) termasuk dalam Mutu I. Kata Kunci: Ayam petelur ISA Brown; Kabupate Sorong; Kualitas Telur; Produksi telur,